FIGURATIVE LANGUAGE USED IN THE "FOREVER YOUNG" SONG LYRIC BY ALPHAVILLE - Habiburrhaman, Muhammad Ihsan; Muhammad, Muhammad; Fitriyah, Fitriyah (Jurnal Ilmiah Bina Bahasa, 2024)
Figurative language is widely used in literary works such as poems, short stories, and novels, enabling authors to convey their ideas in imaginative and creative ways. It goes beyond the literal meaning of words, encouraging readers to use their imagination to uncover deeper interpretations. This research aims to analyze the type of figurative language and to find out the dominant figurative language that is used in the song lyric "Forever Young" by Alphaville. The research method uses a descriptive qualitative method. The data analysis process involves several steps; listening to the song, identifying and categorizing the types of figurative language based on relevant theories, interpreting their meanings through contextual analysis, and finally drawing conclusions. The results are 6 types of figurative language. They are simile (11%), metaphor (32%), personification (14%), hyperbole (21%), alliteration (14%), and idiom (8%). The most dominant type used in the song is metaphor (32%). By understanding and using figurative language appropriately, readers can improve their ability to communicate in English more effectively and attractively.